Техніки та технології створення музичного кліпу - Сльозкіна, Є. А. (ХНУРЕ, 2024)
This thesis dives into the world of making music videos, focusing on how they tell stories visually in today's media landscape. It looks at how music and visuals work together to create emotions, convey messages, and captivate audiences. Through studying films, psychology, and culture, the research into the techniques and creative choices that go into making a music video that really connects with viewers.
Keywords: створення музичного кліпу; музичний кліп